2014
DOI: 10.1089/ten.tea.2013.0277
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Evaluation of PLLA Multichannel Conduits with Nanofibrous Microstructure for the Differentiation of NSCs In Vitro

Abstract: Nerve conduits (NCs) with multiple longitudinally aligned channels, being mimicking the natural nerves anatomical structure, have been attracted more and more attentions. However, some specific structural parameters of a conduit that would be beneficial for further improvement of neural tissue regeneration were not comprehensively considered. Using a systematized device and combining low-pressure injection molding and thermal-induced phase separation, we fabricated 33-channel NCs (outer diameter 3.5 mm, channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…4 shows some promising results considering synthetic biomaterials applied to PNR. From Table 4, it is also possible to find the most recent and relevant reports considering the use of synthetic biomaterials in PNR [87][88][89][90][91][92][93][94][95][96][97][98][99].…”
Section: Suturabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…4 shows some promising results considering synthetic biomaterials applied to PNR. From Table 4, it is also possible to find the most recent and relevant reports considering the use of synthetic biomaterials in PNR [87][88][89][90][91][92][93][94][95][96][97][98][99].…”
Section: Suturabilitymentioning
confidence: 99%
“…PLLA is the crystalline form of PLA. In a study by Zeng et al [89], several topographies were achieved in the PLLA conduit using low-pressure injection molding and thermal-induced…”
Section: Pllamentioning
confidence: 99%
“…In a similar study, PLLA based conduits with nanofibrous structure and microchannels along with higher surface area and lower mechanical strength induced neuronal differentiation of NSCs compared to microporous and ladder-like structures. [211] In addition to the microchannels, longitudinal fibers or surface micropatterns have also been used to provide guided axonal growth and stem cell differentiation. It was reported that changing the alignment, diameter, and surface properties of electrospun PCL microfibers promoted the differentiation of stem cells into Schwann cells or neurons, the secretion of neurotrophins and dictated the morphology and alignment of the derived cells.…”
Section: Conduit/scaffoldmentioning
confidence: 99%
“…In the study of Yang et al, [15] NSCs can progressively grow, migrate and differentiate into neurons throughout a PLLA 3D scaffold fabricated by TIPS. Moreover, multi-channel conduits can be prepared by combining low-pressure injection molding and TIPS, thereby showing great potential applications in nerve-tissue engineering [31,32]. However, polymer crystallization in the liquid solvent during phase separation is the precondition to prepare nanofibrous scaffolds.…”
Section: Nanofibrous Scaffolds By Tipsmentioning
confidence: 99%